1999
DOI: 10.1074/jbc.274.46.32631
|View full text |Cite
|
Sign up to set email alerts
|

p42/p44 Mitogen-activated Protein Kinases Phosphorylate Hypoxia-inducible Factor 1α (HIF-1α) and Enhance the Transcriptional Activity of HIF-1

Abstract: Hypoxia-inducible factor-1 (HIF-1) controls the expression of a number of genes such as vascular endothelial growth factor and erythropoietin in low oxygen conditions. However, the molecular mechanisms that underlie the activation of the limiting subunit, HIF-1␣, are still poorly resolved. Results showing that endogenous HIF-1␣ migrated 12 kDa higher than in vitro translated protein led us to evaluate the possible role of phosphorylation on this phenomenon. We report here that HIF-1␣ is strongly phosphorylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
533
6
13

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 751 publications
(586 citation statements)
references
References 48 publications
34
533
6
13
Order By: Relevance
“…15 However, phosphorylation also seems to play a role as it was shown that ERK1/2 MAPK are important to increase HIF-1 activity in hypoxia in some cell types. 17,18 Since HIF-1 activation by hypoxia occurs in all cell types while ERK1/ 2 is not important for this activation in all of them, other phosphorylation events may take place. In this work, we demonstrated that CK2 could be important for regulating HIF-1 activity in hypoxia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 However, phosphorylation also seems to play a role as it was shown that ERK1/2 MAPK are important to increase HIF-1 activity in hypoxia in some cell types. 17,18 Since HIF-1 activation by hypoxia occurs in all cell types while ERK1/ 2 is not important for this activation in all of them, other phosphorylation events may take place. In this work, we demonstrated that CK2 could be important for regulating HIF-1 activity in hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, phosphorylation events also play a role as demonstrated by several studies: the activity of the MAP kinases ERK1/2 is needed for the transcriptional activity of HIF-1 but not for the stabilization of HIF-1a. 17,18 However, the C-terminal transactivation domain (TAD-C) of HIF-1a is not directly phosphorylated by ERKs 19 but a negative charge on threonine 796, located in the C-terminal transactivation domain of HIF-1a, seems to be essential for the interaction with CBP/p300 and hence for the activity of HIF-1. 20 These results suggest that kinases other than ERK1/2 could be involved.…”
mentioning
confidence: 99%
“…Although the link between the ERK and HIF pathway was identified soon after the discovery of HIFs, the nature of their interplay has remained less clear. Stabilised HIF-1 has been shown to be phosphorylated by p42/44 MAP kinases both under hypoxic conditions and in response to receptor-mediated ERK-activating stimuli [79][80][81]. The ERK-mediated phosphorylation was found to enhance the transcriptional activity of HIF-1 in various model systems, although the exact mechanism is still to be elucidated [82,83].…”
Section: Crosstalk With Erkmentioning
confidence: 99%
“…In particular, ERK1 and ERK2, which are members of the mitogen-activated protein kinase (MAPK) family are thought to be involved in HIF-1 regulation (Ba´rdos and Ashcroft, 2005). ERK1/2 has been shown to phosphorylate HIF-1a in vitro (Richard et al, 1999;Sodhi et al, 2001), whereas it has also been reported that ERK1/2 indirectly enhances HIF-1 activity by phosphorylating p300/CBP and increasing its ability to bind to HIF-1a (Sang et al, 2003). Previous studies have shown that the MEK1/2 inhibitor PD98059 or expression of dominant-negative (DN) forms of Ras, Raf or ERK1/2 all block HIF-1 activity to some degree in multiple cell types (Minet et al, 2000;Sodhi et al, 2001;Lee et al, 2002;Mottet et al, 2002).…”
Section: Introductionmentioning
confidence: 99%